(untitled) (Orfeu, 2023)
Through the information published by the English magazine Guitar News, this article attempts to expose an external view on Brazilian guitar performers and composers, in order to have an overview from the perspective of an international media between the 1950s and 1970s, based on a descriptive documentary research. The information described by the journal displays a kind of prejudice against instrument practices which are not seen as "classical", which seems to influence the selection of the published materials. Therefore, we try to compare each performer’s published repertoire and, through a mapping survey, to analyze quantitatively the nationalities of the composers of the works presented, considering Europe, Brazil and other Latin American countries, in order to understand the possible motivations for the publication of each article. In the introductory section, we present tables with all the editions featuring Brazilian names, in addition to those that were published in the front cover.